Initial maximum push-rim propulsion and sprint performance in elite women's wheelchair basketball: differences between players' functional classification - García-Fresneda, A.; Carmona, G.; Yanci, J.; Iturricastillo, A. (International Journal of Sports Physiology and Performance, 2022)
The aim of the present study was to determine, for the first time in elite women`s wheelchair basketball, the differences in the initial maximum push-rim propulsion (IMPRP), mechanical outputs, and sprint performance between A category (=2.5 class) and B category (=3 class) players. A secondary aim was to assess the association between IMPRP mechanical outputs and sprint performance to determine the influence of specific strength in the latter. Sixteen Spanish women`s wheelchair basketball players participated in this study: A category (n = 9, International Wheelchair Basketball Federation [IWBF] classification range: 1-2.5 points) and B category (n = 7, IWBF classification range: 3-4.5 points). All the players undertook 2 tests: the IMPRP test to measure the strength variables and the 3-, 5-, and 12-m sprint test. B category players reported significantly better performance values in almost all the IMPRP variables and all the sprint distances than A category players. Large to very large significant correlations were observed among IMPRP absolute mechanical outputs (excepting mean power) and sprint performance (3, 5, and 12 m) for all the participants. When the group was divided according to categories A and B, the significant differences observed in the whole group decreased in both groups, although some relationships were large or very large. The IMPRP test and sprint test (3, 5, and 12 m) seemed to be sensitive to differentiate the level between the 2 functional categories. In addition, there was a high association between strength and sprint variables, which shows that greater strength could improve sprint capacity.